Pertanggung Jawaban Pidana terhadap Perawat Maternitas yang Menghilangkan Identitas Seorang Bayi di Rumah Sakit - Edwina Aileen Wirasasmita (University of Udayana, 2018)
Hospitals have their own rules in carrying out the delivery process, the rules contained in the SOPs (Standard Operating Procedures), in the procedure already established procedure for mounting rings for the newborns so the baby can not be confused with the baby other patients and it is the duty of a maternity nurse. The purpose of this study to analyze the criminal liability for a nurse which resulted in an infant being confused because there is still legal uncertainty regarding what constituted a criminal penalty for someone who makes a person's origins unclear because